Hubungan Kualitas Pelayanan Laboratorium Pendidikan dengan Tingkat Kepuasan Mahasiswa di Jurusan Kesehatan Gigi Poltekkes Kemenkes Tasikmalaya - Winda Fratiwi; Lina Rismayanti (THERA-DENT (jurnal terapis gigi dan mulut), 2026)
Background: Educational laboratories are an important means in supporting the learning process of students' practice, especially in health education. The quality of good laboratory services is expected to increase student satisfaction as service users. Objective: This study aims to analyze the relationship between the quality of educational laboratory services and the level of student satisfaction in the Department of Dental Health, Polytechnic of the Ministry of Health, Tasikmalaya. Methods: The study used an analytical quantitative design with a cross-sectional approach. The research sample of 40 IIA level students of the Diploma III Dental Health Study Program was selected using a total sampling technique. The research instrument is in the form of a laboratory service quality questionnaire based on a student satisfaction questionnaire. Data analysis was carried out univariate and bivariate using the Spearman Rank correlation test with a significance level of 5%. Results: Most respondents rated the quality of laboratory services in the categories of good (47.5%) and excellent (42.5%). The level of student satisfaction is in the categories of very satisfied (47.5%) and satisfied (37.5%). The results of the Spearman test showed that there was a significant relationship between the quality of laboratory services and student satisfaction (p=0.000) with a correlation coefficient of 0.756 which showed a strong and positive relationship. Conclusion: The quality of educational laboratory services has a strong relationship with student satisfaction levels. The better the quality of laboratory services, the higher the level of student satisfaction.